Measuring spin polarization of Cu-doped bulk indium tin oxide using point contact Andreev reflection method. - Tan, Lihao. (2009)
Spin polarization of a novel material is of interest to researcher in the field of spintronic devices. Direct measurement of the spin polarization of a novel material using Point Contact Andréev Reflection (PCAR) method is presented. PCAR method is realized using the home-build point contact device.